1987
DOI: 10.1016/0165-4608(87)90211-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic studies of individuals from four kindreds with multiple endocrine neoplasia type II syndrome

Abstract: Multiple endocrine neoplasia type II (MEN-II) syndrome is an autosomal dominant condition characterized by medullary carcinoma of the thyroid, pheochromocytoma, and parathyroid adenoma. A cytogenetic investigation was conducted on 13 MEN-II syndrome patients from four unrelated kindreds and 13 age-matched control subjects for chromosome instability and the chromosome 20 deletion reported in MEN-II syndrome. A significant increase (p < 0.05) was found in the total number of chromatid and chromosome aberrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Silver stain visualizes active nucleolar organizer regions (AgNORs) on the short arms of the five pairs of acrocentric chromosomes in man [1][2][3], Previous studies indicated that there are variations in the size and number of AgNORs between sexes, individuals at different ages and with various disorders including malignancies [4][5][6][7]. The purpose of our cytogenetic investigation was thus to examine AgNORs in cells of a relatively large number of normal individuals of both sexes at various ages as well as patients with multiple endocrine neoplasia-type II (MEN-II), an autosomal dominant malignancy syndrome with increased chromosome breakage characterized by medullary thyroid carcinomas, pheochromocytomas and parathyroid adenomas [8][9][10]. Therefore, we report for the first time AgNOR studies of lymphocytes from normal fetuses and patients with MEN-II and their comparison with control individuals at various ages.…”
Section: Introductionmentioning
confidence: 99%
“…Silver stain visualizes active nucleolar organizer regions (AgNORs) on the short arms of the five pairs of acrocentric chromosomes in man [1][2][3], Previous studies indicated that there are variations in the size and number of AgNORs between sexes, individuals at different ages and with various disorders including malignancies [4][5][6][7]. The purpose of our cytogenetic investigation was thus to examine AgNORs in cells of a relatively large number of normal individuals of both sexes at various ages as well as patients with multiple endocrine neoplasia-type II (MEN-II), an autosomal dominant malignancy syndrome with increased chromosome breakage characterized by medullary thyroid carcinomas, pheochromocytomas and parathyroid adenomas [8][9][10]. Therefore, we report for the first time AgNOR studies of lymphocytes from normal fetuses and patients with MEN-II and their comparison with control individuals at various ages.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood (0.5 ml) was added to 10 ml of RPMI 1640 supplemented with 15% fetal calf serum, penicillin (20 U/ml), streptomycin (20 ug/ml), phytohemagglutinin, and 20 and/or 50 ng/ml mitomycin C (MMC) as previously described. 3,4,5 The cultures were incubated at 37° C for either 48 or 96 hours. Forty-five minutes before harvest, colcemid (0.2 ug/ml-final concentration) was added.…”
Section: Mitomycin C (Mmc)mentioning
confidence: 99%